Redesigning Mobile Application Interface Design Bethesda Hospital with Design Thinking Method: Perancangan Ulang Desain Antarmuka Aplikasi Mobile Rumah Sakit Bethesda Dengan Metode Design Thinking - Asri, Dinda Isnaini; Saputro, Agung Dwi; Budi, Savitri Citra (Procedia of Engineering and Life Science, 2025)
The ease of patient registration process and access to information in hospitals through technology is increasingly in demand. Bethesda Yogyakarta Hospital launched their mobile application in 2017, avaiable on Google Play Store and App Store. User responses varied from positive to negative. Some users gave negative responses, namely less user-friendly, limited features, and simple design compared to its competitors. To overcome this, this study aims to redesign the interface design of the Bethesda Hospital Mobile Application by prioritizing user needs through a design thinking approach. This research is categorized as Research and Development (R&D) and involves various data collection methods, including interviews, documentation studies, competitive analysis, and survey distribution. Data validity used source triangulation by involving the IT department of Bethesda Hospital Yogyakarta. At the empathize stage, researchers identified problems and user needs related to information and features that need to be improved. At the define stage, core problems were formulated, including adding application functions, features, information, and interface design. At the ideate stage, researchers generated creative ideas for application development solutions. At the prototype stage, a visualization design was created based on the the design development ideas. In the testing stage, the test results showed that users completed the scenario tasks, but there were still tasks that required more time to complete. This research resulted in a redesign of the Bethesda Hospital Mobile Application interface that can be used as a development reference. The application of each stage of the design thinking method can be used to design other information technology applications.